Rancang Bangun Antena Stacked turnstile Pada Frekuensi 2,4 GHz Untuk Aplikasi WIreless Local Area Network (WLAN) - Erwan Dian Sitoresmi; waluyo waluyo; Koesmarijanto Koesmarijanto (Politeknik Negeri Malang, 2015)
The purpose of this research is to design an antenna that will be used as a transmitting antenna that can level up the receiver. The designed antenna is a stacked turnstile antenna that has again of 3dB from previous studies. At the turnstile antenna using a power divider to raise the antenna gain of 1.5dB. Power divider is used Wilkins on power divider with a vertical stack. The stack distance used is0.6?. From the results of the implementation of the AntennaLaboratory of the Polytechnic of Malang, a stacked turnstile antenna produces vertical polarization and omnidirectional radiation patterns. Value of the measured return loss is-13.8dBat a frequency of 2,384MHz. Additionally stacked turnstile antenna has a value of 4.83dBi gain. VSWR values were measured at a frequency of 2,384GHz is 1,091 and has 425MHz bandwidths frequencies ranging from 2275 to 2700MHz. Level of signal reception at the access point-Link TL Type WA 5110G higher than 4dbm antenna access point, while stacked turnstile antennas transmitting antenna at a maximum distance of 100m to get the signal reception is better than 84dB antenna access point signal reception-89dB.